Kurtöp case: the pragmatic ergative and beyond - Hyslop, Gwendolyn (2024)
Kurtöp, an East Bodish language of Bhutan, uses case markers for a variety of functions. Like many Tibeto-Burman languages, Kurtöp evidences an ergative whose functions extend above and beyond the typical role of distinguishing the A argument in a bivalent clause. The Kurtöp ergative signals the A argument in some bivalent clauses and denotes a variety of pragmatic and semantic functions in both monovalent and bivalent clauses. In bivalent clauses, a set of verbs also exhibit differential object marking, employing a locative case-marker to designate various types of pragmatic focus.